Biochar for Improving crop Production in Nepal - Vista, S P; Pandit, N R (SAARC Journal of Agriculture, 2023)
Improving soil fertility and crop productivity is crucial to reduce food insecurity and poverty in Nepal. Biochar as a soil amendment has been found effective in increasing crop production. Here, we reviewed various biochar studies carried out in Nepal by different organizations and assessed future potential of biochar as an effective soil amendment. In this review, we have included the biochar pretreated (enriched) with nutrient or added separately in soil. We found that good quality biochar could be produced using the novel flame curtain metal and soil pit “Kontik” kiln with slow pyrolysis technology. Biochar produced from Kontiki found having high pH (9.8), organic carbon (OC, 72%), surface area (215 m2g-1) and cation exchange capacity (CEC, 72 cmol kg-1). Further, biochar application improved soil chemical properties (pH, OC, CEC, base cations) and nutrient availability such as available phosphorous (P) and potassium (K). Similarly, biochar addition increased crop yield significantly compared with non-biochar plots. Higher crop yield was achieved when biochar was enriched or charged with cattle urine. Thus, from this study, we suggest that biochar should be prioritized in government programs as a potential soil amendment and scale up or increase its use at farm level. SAARC J. Agric., 21(1): 227-238 (2023)